Reducing Bias in Emergency Medicine Chart Review Studies: Looking Through the Retrospectoscope (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this article is to: identify the various processes in chart review studies that can introduce bias; describe the steps an investigator may take when planning a chart review study to mitigate distortion and bias; and describe reporting techniques that maximise transparency so readers can anticipate the biases and the study's limitations. It is yet unknown how electronic medical records will ultimately affect retrospective research. By using boilerplates, copying and pasting information, using pre-checked boxes, and delaying time stamps in relation to actual care, new biases may be introduced. This article offers guidelines for conducting and documenting studies in which chart review is a method of data collecting. Our main reporting suggestion is to be honest and state precisely what was done and what was discovered for each subject discussed in articles. The scientific method's guiding principles, which stress the value of documenting a study in enough detail to allow replication, directly inform this advice.